INTERPRETASI LAGU-LAGU NADIN AMIZAH (ALBUM SELAMAT ULANG TAHUN): KAJIAN SEMIOTIKA - dan Syamsul Anwar, Afsun Aulia Nirmala (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2020)
Lyrics are literary works that contain an outpouring of personal feelings. In heuristic reading, rhymes are read based on language conventions or language systems in accordance with the position of language as a first level semiotic system. The study of signs and how they work is called semiotics. Semiotics study is a science or method of analysis to study signs. In this analysis, we look for the meaning of the lyrics of Nadin Amizah's songs in the album Happy Birthday through semiotic and matrix readings and models of Nadin Amizah's songs in the album Happy Birthday. The result of this analysis is that the song written is a picture of Nadin Amizah's life that experienced several problems in her life. It can be concluded that the matrix contained in each song is in the refresh.